Solid and Cystic Tumor (SCT) of the Pancreas in an Adult Man. Issue 5 (1997) - Ohiwa, K.; Igarashi, M.; Nagasue, N.; Nagasaki, M.; Harada, T.
Abstract : Solid and cystic tumor (SCT) of the pancreas predominantly Occurs in women, and the occurrence in men is extremely rare. We experienced a male case of SCT. A 38-year-old man was admitted with the complaint of upper abdominal pain. CT scan showed the presence of a mass in the head of the pancreas. The mass was composed of high density areas and low density areas. Ultrasonograms revealed the mass being composed of high echoic areas and low echoic areas. The mass .was hypovascular on angiography. SCT was suspected and pancreaticoduodenectomy was performed. The cut surface of the tumor showed mainly cystic degenerative areas containing dark red hemorrhagic materials. Microscopically, there were solid areas in the periphery and pseudopapillary areas in the center. No metastasis was found in the removed lymph nodes. The tumor cells were not stained by Grimelius' silver stain. The tumor cells were positive for alpha-l-antitrypsin (AAT) and neuron-specific enolase (NSE). Pancreatic hormones such as insulin, glucagon, and somatostatin were all negative. Electron micrograph showed that tumor cells were rich in mitochondria. Zymogen granules and neurosecretory granules were not detected. Estrogen receptor (ER) and progesterone receptor (PR) were both negative.